2020
DOI: 10.1186/s12889-020-09468-w
|View full text |Cite
|
Sign up to set email alerts
|

Community health workers impact on maternal and child health outcomes in rural South Africa – a non-randomized two-group comparison study

Abstract: Background Home visits by paraprofessional community health workers (CHWs) has been shown to improve maternal and child health outcomes in research studies in many countries. Yet, when these are scaled or replicated, efficacy disappears. An effective CHW home visiting program in peri-urban Cape Town found maternal and child health benefits over the 5 years point but this study examines if these benefits occur in deeply rural communities. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 39 publications
(50 reference statements)
0
14
1
Order By: Relevance
“…The interventions provided mixed results. When undertaken in a peri-urban area in which participants received visits from community health workers, the intervention was found to reduce maternal depression at 6-month follow-up when compared standard available care [79]. However, a similar intervention, undertaken in a rural area, found no significant differences regarding maternal depression scores between groups in the first 2 years postpartum [80].…”
Section: Discussionmentioning
confidence: 99%
“…The interventions provided mixed results. When undertaken in a peri-urban area in which participants received visits from community health workers, the intervention was found to reduce maternal depression at 6-month follow-up when compared standard available care [79]. However, a similar intervention, undertaken in a rural area, found no significant differences regarding maternal depression scores between groups in the first 2 years postpartum [80].…”
Section: Discussionmentioning
confidence: 99%
“…CHWs or lay healthcare workers are typically community members who are trusted and respected, and able to provide a link between people's homes and formal government primary healthcare clinics (Olaniran et al, 2017). Clinical trials and longitudinal observational studies of visits by CHWs have shown to improve maternal well‐being (including symptoms of maternal depression) and child development in low‐resource settings (Kumar et al, 2020; le Roux et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…After completion of training, FCHVs are provided a certificate from the Ministry of Health, and a medicine kit that includes oral rehydration solution packets and oral supplements such as vitamin A and iron. They are provided an identity card and a register with 30 to 40 indicators to be recorded, including maternal, infant, and child deaths, and details of vertical programmes in their areas [7,39].…”
Section: Female Community Health Volunteers Of Nepalmentioning
confidence: 99%
“…In 2011, the South African (SA) National Department of Health (NDOH) launched 'The Re-engineering of Primary Health Care' policy, which relies heavily on CHWs, to reduce maternal and child mortality and improve access to health care [39,40]. Local communities and Non-Governmental Organizations (NGOs) responded to overwhelming care and social needs in the HIV-affected countries of southern Africa and provided home-based care and support that emerged organically.…”
Section: The Community Health Workers In South Africamentioning
confidence: 99%